2021
DOI: 10.3389/fendo.2021.774260
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Differences Between Zona Pellucida-Bound and Manually Selected Spermatozoa Are Associated With Autism Susceptibility

Abstract: Children conceived through intracytoplasmic sperm injection (ICSI) have been reported to have a higher risk of many abnormalities and disorders, including autism and intellectual disability, which may be due to bypassing of the natural sperm selection process during ICSI. Zona pellucida (ZP)-bound spermatozoa (ZPBS) have normal morphology and nuclear DNA. Using these spermatozoa for ICSI results in better outcomes compared with conventional ICSI. However, differences besides morphology that exist between sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The examination of methylation status at specific loci might definitively answer the question as to whether hypomethylation or hypermethylation is the major factor leading to suboptimal ZP-binding ability. To pinpoint the specific locus associated with ZP-binding ability, future investigation is needed to examine the DNA methylation profile of ZP-bound spermatozoa by single-cell bisulfite sequencing ( 109 , 110 ). While the complicated staining and quantification procedures restrict wide application of genetic evaluation in clinical settings, future investigation should seek to develop a highly robust, indirect evaluation of sperm quality metrics by image analysis of sperm morphology associated with genetic integrity ( 111 ) and epigenetic pattern to establish a comprehensive profile of clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…The examination of methylation status at specific loci might definitively answer the question as to whether hypomethylation or hypermethylation is the major factor leading to suboptimal ZP-binding ability. To pinpoint the specific locus associated with ZP-binding ability, future investigation is needed to examine the DNA methylation profile of ZP-bound spermatozoa by single-cell bisulfite sequencing ( 109 , 110 ). While the complicated staining and quantification procedures restrict wide application of genetic evaluation in clinical settings, future investigation should seek to develop a highly robust, indirect evaluation of sperm quality metrics by image analysis of sperm morphology associated with genetic integrity ( 111 ) and epigenetic pattern to establish a comprehensive profile of clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy among the overlapping DMRs between this paternal sperm study and the DDE DMRs reported here is the extensive methylation differences in the noncoding SNORD115 region on chromosome 15 that are further discussed below. It is also notable that DNA methylation differences between zona pellucida-bound sperm and manually selected sperm (typically used for intracytoplasmic sperm injection (ICSI) methods to treat infertility) were enriched for genes involved in ASD and neurogenesis, especially in regions with bivalent chromatin structure ( Wang et al, 2021 ). These findings may explain the higher risk of ASD that is associated with ICSI ( Kissin et al, 2015 ; Djuwantono et al, 2020 ), and further suggest a potential paternal contribution to ASD based on the sperm methylome.…”
Section: Discussionmentioning
confidence: 99%
“…Children conceived ART show a slight increase in a possible psychiatric diagnosis compared to those conceived spontaneously. Studies have identified an increased risk of ASD in children born after the ICSI procedure compared to conventional IVF [23,24], because the ICSI procedure using manually selected spermatozoa increases the risk of autism gene methylation mutations compared to the one using zona pellucidabound spermatozoa [25].…”
Section: Infertility Drugs and Asdmentioning
confidence: 99%